2018
DOI: 10.2147/cmar.s159090
|View full text |Cite|
|
Sign up to set email alerts
|

L61H46 shows potent efficacy against human pancreatic cancer through inhibiting STAT3 pathway

Abstract: BackgroundPancreatic cancer is the fourth leading cause of cancer-related death worldwide. The poor prognosis of this disease highlights the urgent need to develop more effective therapies. Activation of the STAT3 represents a potential drug target for pancreatic cancer therapy. Currently, clinically available small-molecule inhibitors targeting STAT3 are lacking.MethodsThrough bioassay screening and molecular docking, we identified a small molecule L61H46 that can potently target constitutive STAT3 signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…Based on the important role of STAT3 in the process of NSCLC and the structural similarity of Rhein with the four known inhibitors of STAT3 (Napabucasin, STA-21, LLL12 and LY5), we thought that Rhein may affect the phosphorylation of STAT3 11,21. We tested the inhibiting ability of Rhein on STAT3 phosphorylation (P-STAT3) in NSCLC cells.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the important role of STAT3 in the process of NSCLC and the structural similarity of Rhein with the four known inhibitors of STAT3 (Napabucasin, STA-21, LLL12 and LY5), we thought that Rhein may affect the phosphorylation of STAT3 11,21. We tested the inhibiting ability of Rhein on STAT3 phosphorylation (P-STAT3) in NSCLC cells.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of STAT3 using small molecules or RNAi reduced cancer cell proliferation, migration and invasion, and induced apoptosis in vitro [179,[255][256][257], whilst reducing tumour growth and angiogenesis in vivo [256,258]. Liposomal delivery of a small molecule STAT3 inhibitor reduced STAT3 activation and cell growth, and sensitised cells to radiotherapy and chemotherapy in vitro and in vivo [240].…”
Section: Do Il-6 Family Cytokines Represent a New Therapeutic Opportumentioning
confidence: 99%
“…An increasing number of studies have shown that abnormal activation of STAT3 occurs in a variety of drug-resistant cells, and inhibition of STAT3 can reverse drug resistance 17. Therefore, STAT3 is deemed as an attractive target for antitumor drug development 21,22…”
Section: Discussionmentioning
confidence: 99%